Evaluation of resistive index using color Doppler imaging of orbital arteries in geriatric patients with hypertension - Ali Akal (Indian Journal of Ophthalmology, 2014)
Background and Aim: Resistive index (RI) is an indirect measurement of blood flow resistance that can be used to evaluate vascular damage in ophthalmologic disease. The purpose of this study was to evaluate the association between RI values of orbital arteries using the color Doppler imaging (CDI) in geriatric hypertensive patients with or without retinopathy. Setting and Design: Designed as a cross-sectional study. Materials and Methods: We evaluated 60 geriatric patients with hypertension (Group 1) and 30 healthy subjects (Group 2). Further, the patients with hypertension were grouped into two: Group 1a consisted of patients with retinopathy (n = 30), and group 1b consisted of patients without retinopathy (n = 30). The mean RI values of ophthalmic artery (OA), central retinal artery (CRA), and posterior ciliary artery (PCA) were measured using CDI. Results: Compared to group 2, group 1 had significantly higher mean resistive index of PCA levels (P = 0.017), whereas there were no statistical difference in mean resistive indexes of OA and CRA (both P > 0.05). Besides, there were no statistical difference in mean resistive indexes of OA, CRA, and PCA between the group 1a and group 1b (P > 0.05 for all). Mean resistive indexes of OA, CRA, and PCA were significantly correlated with the duration of hypertension (r = 0.268, P = 0.038; r = 0.315, P = 0.014; r = 0.324, P = 0.012, respectively). Conclusions: Our study indicates that RI might be a useful marker for the ocular hemodynamic of retinal vessels, provides morphologic and vascular information in hypertension and hypertensive retinopathy.